The role of distinction, necessity and proportionality in Afghan civilians' attitudes towards wartime harm - Dill, J (Cambridge University Press, 2019)
How do civilians react to being harmed in war? Existing studies argue that civilian casualties are strategically costly because civilian populations punish a belligerent who kills civilians and support the latter's opponent. Relying on eighty-seven semi-structured interviews with victims of coalition attacks in Afghanistan, this article shows that moral principles inform civilians’ attitudes toward their own harming. Their attitudes may therefore vary with the perceived circumstances of an attack. Civilians’ perception of harm as unintended and necessary, in accordance with the moral principles of distinction and necessity, was associated with narratives that cast an attack as relatively more legitimate and with a partial or full release of the coalition from blame. The principle of proportionality, which requires that civilian casualties are caused in pursuit of a legitimate war aim, informed their abstract attitudes toward civilian casualties in Afghanistan. Two rules of international law, which accord with the moral principles of distinction and necessity, were reflected in the civilians’ attitudes. The legal rule of proportionality, which diverges from the namesake moral principle, failed to resonate with the civilians. The article explores whether compliance with the legal rules of distinction and necessity can contribute to mitigating the strategic costs of civilian casualties.